Structural characterization of 3-dehydroquinate synthase II : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science majoring in Biochemistry at the Institute of Fundamental Sciences, Massey University, Turitea, Palmerston North, New Zealand - Somerton, Jack (Massey University, 2016)
Aromatic amino acids tryptophan, tyrosine and phenylalanine are derived from a common precursor, chorismate, which is produced by the seven-step shikimate pathway in plants, fungi, Bacteria and Archaea. In Archaea the shikimate pathway typically begins with the alternative substrates, L-aspartate semialdehyde and 6-deoxy-5-ketofructose-1-phosphate, and so requires different enzymes to catalyse the first two steps in the pathway compared to those used in the (common) bacterial pathway. The archaeal enzyme for the second step, 3-dehydroquinate synthase type 2 (DHQS2), catalyses the oxidative deamination of 2-amino-3, 7-dideoxy-D-threo-heptoulsonic acid (formed in step 1) followed by cyclisation to produce 3-dehydroquinate, at which point the alternative and common shikimate pathways converge. No DHQS2 structures have yet been determined, and because DHQS2 enzymes have little sequence homology with their DHSQ1 analogues, they may have a novel fold. Bioinformatic methods were used to predict the solubility, stability and likelihood of sequenced DHQS2s to form crystals, and the five highest ranked were chosen for structural studies. Methanococcus maripaludis, Desulfatibacillum alkenivorans, Methanospirillum hungatei, and Archaeoglobus veneficus DHQS2 open reading frames were amplified by PCR and cloned into a modified pETite32a(+) vector in order to produce recombinant protein with an N-terminal, a C-terminal or no His8-tag. Soluble recombinant DHQS2 proteins were produced in Escherichia coli DL41 (DE3), then purified by immobilized metal-ion affinity chromatography followed by size exclusion chromatography. C-terminally-tagged M. maripaludis DHQS2 with bound cofactor NAD+ crystallised in two conditions: (i) 1.0 M ammonium sulfate, 0.1 M Bis-Tris pH 5.5 with 1% (w/v) PEG 3350; and (ii) 0.1 M CAPS at pH 10.5 with 40% (v/v) 2-methyl-2,4-pentanediol, but unfortunately the crystals were not of diffraction quality. Structure prediction using bioinformatic tools and/or far and near Circular Dichroism spectroscopy indicated that recombinant M. maripaludis DHQS2 was likely to have a secondary structure dominated by α-helices and had tertiary structure; recombinant A. veneficus was likely to have a secondary structure dominated by β-strands and had tertiary structure, while recombinant D. alkenivorans, and M. hungatei were more likely to assume a molten globule structure dominated by β-strands.
Keywords: Lyases; Bioorganic chemistry; Research Subject Categories::NATURAL SCIENCES::Chemistry::Biochemistry